2022
DOI: 10.1371/journal.pgen.1010228
|View full text |Cite
|
Sign up to set email alerts
|

An in vivo drug repurposing screen and transcriptional analyses reveals the serotonin pathway and GSK3 as major therapeutic targets for NGLY1 deficiency

Abstract: NGLY1 deficiency, a rare disease with no effective treatment, is caused by autosomal recessive, loss-of-function mutations in the N-glycanase 1 (NGLY1) gene and is characterized by global developmental delay, hypotonia, alacrima, and seizures. We used a Drosophila model of NGLY1 deficiency to conduct an in vivo, unbiased, small molecule, repurposing screen of FDA-approved drugs to identify therapeutic compounds. Seventeen molecules partially rescued lethality in a patient-specific NGLY1 deficiency model, inclu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 50 publications
(90 reference statements)
3
10
0
Order By: Relevance
“…More in-depth study in a dopaminergic neuronal model of NGLY1 disease is required to understand the disruption of the dopaminergic system in NGLY1 disorder. Non-etheless, our results are consistent with findings from two drug repurposing screens in worm ( Iyer et al, 2019 ) and fly models of NGLY1 deficiency ( Hope et al, 2022 ), which identified compounds that modulate the dopamine pathway to reverse NGLY1 related phenotype. Additionally, the NGLY1 deficient organoids showed a reduction in GABA neurotransmitter up to day 45.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…More in-depth study in a dopaminergic neuronal model of NGLY1 disease is required to understand the disruption of the dopaminergic system in NGLY1 disorder. Non-etheless, our results are consistent with findings from two drug repurposing screens in worm ( Iyer et al, 2019 ) and fly models of NGLY1 deficiency ( Hope et al, 2022 ), which identified compounds that modulate the dopamine pathway to reverse NGLY1 related phenotype. Additionally, the NGLY1 deficient organoids showed a reduction in GABA neurotransmitter up to day 45.…”
Section: Discussionsupporting
confidence: 86%
“…Despite multiple studies performed in model organisms ( Tambe et al, 2019 ; Han et al, 2020 ; Talsness et al, 2020 ), the pathogenesis of NGLY1 deficiency is still poorly understood. Recent studies focusing on neurological phenotypes of NGLY1 disorder have shown disruptions in ion channels, monoamine pathways and dysregulation in stress responses ( Owings et al, 2018 ; Mueller et al, 2020 ; Hope et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Larvae were imaged at 2.5× magnification using a Leica EC3 camera. Larval size was quantified using ImageJ as previously described ( Hope et al 2022 ). All larval measurements were performed with at least 20 larvae per genotype.…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, the broad scope of ES/GS can, in rare instances, dramatically expedite diagnosis-specific interventions for patients who present with a nonspecific phenotype ( 73 ). Further, the rapid identification of specific variants fostered innovative interventions such as the repurposing of existing medications to target the biochemical pathway impacted by pathogenic variants ( 74 , 75 ), and the development of antisense oligonucleotides targeted to specific pathogenic variants that inhibit aberrant protein production ( 76 ). With better refinement of NGS technologies, these tangible benefits to patients are likely to increase.…”
Section: Impact Of Exome and Genome Sequencing On Undiagnosed Syndromesmentioning
confidence: 99%